2021
DOI: 10.3389/fphar.2021.685176
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Experience of mTOR Inhibitors in Liver Transplant Recipients in a Region Where Living Donation Is Predominant

Abstract: Background: Mammalian target of rapamycin (mTOR) inhibitors, such as everolimus and sirolimus, may be efficacious in preserving renal function in liver transplantation (LT) recipients while preventing hepatocellular carcinoma (HCC) recurrence.Materials and Methods: In this study, we retrospectively evaluated the safety, efficacy, and renoprotective effects of mTOR inhibitors in LT recipients. Among the 84 patients enrolled, mTOR inhibitor was commenced during the first year after LT. Renal function was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To examine the mechanism by which LncTUG1 may promote HCC progression, we first selected genes related with LncTUG1 and make GO enrichment analysis in StarBase ( http://starbase.sysu.edu.cn ) and Metascape ( http://metascape.org/gp/index ). On account of it remarkably affects the evolement of HCC 23 25 , the mTOR/S6K pathway was selected for study (Fig. 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the mechanism by which LncTUG1 may promote HCC progression, we first selected genes related with LncTUG1 and make GO enrichment analysis in StarBase ( http://starbase.sysu.edu.cn ) and Metascape ( http://metascape.org/gp/index ). On account of it remarkably affects the evolement of HCC 23 25 , the mTOR/S6K pathway was selected for study (Fig. 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…The findings from this follow-up study in the LDLT setting further demonstrated that early conversion to an EVR-based regimen improves/preserves renal function, both immediately and long-term. A recent retrospective real-world study showed that patients with renal impairment experienced significant improvement in renal function after conversion to mTOR inhibitor [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Sung et al [ 19 ] found that individuals with impaired renal function improved significantly after 12 mo of using mTOR inhibitors. The median eGFR values at 1, 3, 6, and 12 mo after switching to mTOR inhibitors were 90, 75.5, 74.5, and 76.8 mL/min.…”
Section: To the Editormentioning
confidence: 99%